Identification of Restricted Use Areas (AURs) in the Triângulo Mineiro/Alto Paranaíba region under an integrated environmental approach (Revista Espinhaço, 2026)
The Brazilian Forest Code defines Restricted Use Areas (AURs) as marsh plains and areas with slopes of 25° to 45°, allowing agricultural activities and sustainable forest management. This study aims to propose a methodology for delimiting AURs in the Triângulo Mineiro/Alto Paranaíba, Minas Gerais, using the QGIS 3.36.3 software and data from Digital Elevation Models (Alos Palsar). Land use and land cover analysis was performed with the MapBiomas 8.0 collection, assessing the conservation status of AURs and correlating soil types. We identified 41,732 hectares of AURs, of which 51.76% are occupied by land use and pasture mosaics. Regarding soils, 21.04% are on Haplic Cambisols and 40.17% on Red Latosols. It was observed that AURs often coincide with areas of climate vulnerability and biomes considered biodiversity hotspots. The methodology presented uses public and official data, providing a practical tool for environmental managers and landowners to identify AURs on sloping terrains. The proposal is essential for local land use planning and environmental conservation strategies, with the potential to be replicated in other regions of Brazil.
Keywords: Environmental Planning; Precision Agriculture; Remote Sensing; Agricultural Sciences